A three-dimensional clustered peer-to-peer overlay protocol for mobile ad hoc networks. (September 2021) - Tahir, Ali; Shah, Nadir; Abid, Shahbaz Akhtar; Khan, Wazir Zada; Bashir, Ali Kashif; Zikria, Yousaf Bin
Abstract: Peer-to-peer (P2P) computing involves exchanging resources and files by computers connected through a network rather than a central server. In P2P, over mobile ad hoc networks (MANETs), the fundamental necessity is the linkage of the overlay participating peers (OPPs) for the efficient operation of the DHT-based P2P overlay protocol over MANETs. This necessity becomes more critical in a high mobility environment. Due to the high mobility of OPPs, the topology of the P2P overlay is altered continuously. Consequently, the efficiency of DHT-based P2P overlay protocol over MANETs greatly decreases due to the increased lookup latency, maintenance, computational, and control overheads. In the current research, a novel three-dimensional clustered overlay P2P protocol, i.e., 3DCOP, is suggested to cope with the identified issues. Simulation results depict that 3DCOP performs better in routing overhead, false-negative ratio, path-stretch ratio, and file discovery delay in the high mobility environment over MANETs. Graphical abstract: Highlights: Develop an effective DHT-based peer-to-peer overlay clustering mechanism. Works at application layer over mobile ad hoc networks considering high node mobility. Present an effective novel replica management strategy that minimizes the lookup latency. Reduce routing, control, and computational overheads. Curtailing the path-stretch-penalty to avoids indispensable prolonged paths. Offering greater flexibility in choosing a path from source to destination.